2023
DOI: 10.1002/ejp.2163
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic risk factors for long‐term opioid use: A national registry‐linkage study

H. H. Nestvold,
S. S. Skurtveit,
A. Hamina
et al.

Abstract: BackgroundOpioid use has increased substantially as a treatment for chronic pain, although harms from long‐term opioid therapy outweigh the benefits. More knowledge about factors associated with long‐term opioid use is needed. We aimed to investigate the association between socioeconomic status and long‐term opioid use in the period 2010–2019.MethodsThis was a nested case–control study in which the cases were all persons ≥18 years with long‐term opioid use, that is use of opioids for more than 3 months (N = 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…A recent study on adults in Norway found that socioeconomic factors remain strongly associated with long-term opioid use, also when accounting for pain conditions and mental health diagnoses. 52 Our finding that childhood trauma exposure was associated with higher analgesics prescription rates after adjustment for socioeconomic factors could indicate that the higher prevalence of childhood trauma among children growing up with a lower socioeconomic status is a driving force behind the observed higher risk of long-term opioid use in this group.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A recent study on adults in Norway found that socioeconomic factors remain strongly associated with long-term opioid use, also when accounting for pain conditions and mental health diagnoses. 52 Our finding that childhood trauma exposure was associated with higher analgesics prescription rates after adjustment for socioeconomic factors could indicate that the higher prevalence of childhood trauma among children growing up with a lower socioeconomic status is a driving force behind the observed higher risk of long-term opioid use in this group.…”
Section: Discussionmentioning
confidence: 69%
“…Socioeconomic factors increasing risk of trauma exposure may also increase risk of receiving long-term opioid prescriptions. 52 Despite national variations in prescription practices, it is observed that patients with psychosocial problems receive more opioid prescriptions than individuals without such problems. 13 , 58 , 62 This study was conducted in Norway, where prescription rates for opioids are generally low 33 and health care is accessible and affordable.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, SES and place of residency were univariately associated with sustained opioid use, but these associations were nullified in the multivariable analysis. Low SES is known to be positively associated with sustained use in adults, 1,8,36,39 but most studies in children and adolescents on sustained opioid use do not include SES as a variable. 4,16,48 Nonetheless, a recent study, performed in children and young adults with kidney stones, found sociodemographic factors to be unrelated to sustained use.…”
Section: Discussionmentioning
confidence: 99%